The Duties & Functions of the Internal Prosecutor's Intelligence Disclosing on Corruption Crime - Iwan Mex Namara; Amin Purnawan; Ira Alia Maerani (Law Development Journal, 2022)
The purpose of this paper is to find out, examine and analyze the duties and functions of the Public Prosecution Service in uncovering criminal acts of corruption. This research used a normative juridical method with research specifications in the form of descriptive analysis. Based on the discussion, it was concluded that Article 130 of the Decree of the Attorney General of the Republic of Indonesia Number: Kep– 225/A/JA/05/2003 stated that the Deputy Attorney General for Intelligence has the duty and authority to carry out judicial intelligence activities in the social, political, economic, financial, defense fields/security and public order to support law enforcement and justice policies, both preventive and repressive. In general, the handling of corruption cases has 3 roles, the first being in repressive efforts, namely by conducting investigations into criminal acts of corruption, second, in preventive efforts or prevention of criminal acts of corruption by forming the Guard and Security Team for Regional Government and Development (TP4D), and third, in the search for fugitives from the Prosecutor's Office or Court. Regarding the analysis of the Prosecutor's Intelligence, after the Task Order was issued and signed by the Head of the District Attorney's Office, the Intelligence Section of the Prosecutor's Office took a series of actions by making an Analysis of Targets (Ansas), Analysis of Tasks (Antug) and Targets of Operations (TO).